2016
DOI: 10.1016/j.humov.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Progressive reduction versus fixed level of support during training: When less is less

Abstract: Previous empirical and theoretical work suggests that effective skill acquisition requires movements to be generated actively and that learning new skills supports the acquisition of prospective control. However, there are many ways in which practice can be structured, that may affect the acquisition and use of prospective control after training. Here, we tested whether the progressive modulation and reduction of support during training was required to yield good performance after training without support. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, there are limits to this notion. Snapp-Childs, Wang and Bingham (2016) demonstrated that generating a high number of errors during training led to good learning but not better learning that when generating a moderate number of errors – and contrary to Williams and Carnahan's assertions, generating more errors did not appear to “speed up” learning. In fact, even when training young, healthy adults (as in Snapp-Childs et al, 2015), more errors appeared to be more of a nuisance during training rather than a learning booster.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, there are limits to this notion. Snapp-Childs, Wang and Bingham (2016) demonstrated that generating a high number of errors during training led to good learning but not better learning that when generating a moderate number of errors – and contrary to Williams and Carnahan's assertions, generating more errors did not appear to “speed up” learning. In fact, even when training young, healthy adults (as in Snapp-Childs et al, 2015), more errors appeared to be more of a nuisance during training rather than a learning booster.…”
Section: Discussionmentioning
confidence: 62%
“…This was an important finding because the training task was relatively difficult for the children (with motor difficulties) to perform and children typically become averse to interventions if they are too challenging. Our approach, however, was designed to keep enjoyment and self-efficacy high throughout the intervention by keeping levels of performance relative high; thus, avoiding the aversion in the first place (Snapp-Childs et al, 2016). …”
Section: Discussionmentioning
confidence: 99%